2013
DOI: 10.1002/ca.22226
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative trends of the palmaris longus muscle in a South African population

Abstract: The literature reports that the palmaris longus muscle (PL) is only found in mammals in which the forelimbs are weight-bearing extremities. It is suggested that the function of this muscle has been taken over by the other flexors in the forearm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 14 publications
3
18
1
8
Order By: Relevance
“…A total of 26 articles (Machado and DiDio, 1967;Troha et al, 1990;Ceyhan and Mavt, 1997;Thompson et al, 2001;Sebastin et al, 2006;Roohi et al, 2007;Abu Hassan, 2008;Kapoor et al, 2008;Kayode et al, 2008;Kose et al, 2009;Gangata, 2009;Mbaka and Ejiwunmi, 2009;Agarwal, 2010;Erić et al, 2010Erić et al, , 2011Ndou et al, 2010;Sater et al, 2010;Erić et al, 2011;Ertem et al, 2011;Hiz et al, 2011;Kigera and Mukwaya, 2011;Sankar et al, 2011;Kyung et al, 2012;Soltani et al, 2012;Abdel Raouf et al, 2013;Lahiji et al, 2013;Venter et al, 2013) were included for review (Tables 1 and 2).…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 26 articles (Machado and DiDio, 1967;Troha et al, 1990;Ceyhan and Mavt, 1997;Thompson et al, 2001;Sebastin et al, 2006;Roohi et al, 2007;Abu Hassan, 2008;Kapoor et al, 2008;Kayode et al, 2008;Kose et al, 2009;Gangata, 2009;Mbaka and Ejiwunmi, 2009;Agarwal, 2010;Erić et al, 2010Erić et al, , 2011Ndou et al, 2010;Sater et al, 2010;Erić et al, 2011;Ertem et al, 2011;Hiz et al, 2011;Kigera and Mukwaya, 2011;Sankar et al, 2011;Kyung et al, 2012;Soltani et al, 2012;Abdel Raouf et al, 2013;Lahiji et al, 2013;Venter et al, 2013) were included for review (Tables 1 and 2).…”
Section: Search Resultsmentioning
confidence: 99%
“…African. Seven studies reported the overall PLA rate in Africans (Kayode et al, 2008;Gangata, 2009;Mbaka et al, 2009;Ndou et al, 2010;Kigera and Mukwaya, 2011;Soltani et al, 2012;Venter et al, 2013) with a total of 3,907 subjects. The pooled proportion of the random effects distribution for studies of PLA was 11.3% (95% CI 5 0.037-0.222) with Q 5 499.52, df 5 6, P < 0.0001, I 2 5 98.8%.…”
Section: Ethnicitymentioning
confidence: 99%
See 2 more Smart Citations
“…According to Eric et al, the middle-age and young group showed a lower rate of the PLM presence as compared to the old group, although this difference was not significant [36,38]. In comparison, Venter et al reported no obvious trend in the PLM in the various age groups that would indicate phylogenetic degeneration of the PLM [39].…”
Section: Discussionmentioning
confidence: 96%